Analisis pengelolaan sampah pasar tradisional di Pasar Gegerkalong, Kota Bandung, Indonesia - Silfia, Regina; Surtikanti, Hertien Koosbandiah (Journal of Waste and Sustainable Consumption, 2024)
Background: The issue of waste is intricately linked to behavior and lifestyle patterns. The increased activity in markets leads to a rise in the accumulation of waste in their vicinity. Traditional markets possess significant potential for generating organic waste such as leftover vegetables, fruits, and food items. However, the management of organic waste in traditional markets remains inadequate. This is primarily attributed to the lack of awareness and knowledge among market traders regarding the issues arising from organic waste. Methods: This research takes a qualitative approach, collecting data through observation, interviews, and questionnaire distribution. Findings: The findings reveal the ineffectiveness of waste management in markets. Conclusion: There is a need for efforts to provide education and ensure proper waste management to prevent environmental pollution in market areas.